Method for preparing neodymium iron boron permanent magnet through composite diffusion

Through composite diffusion technology, using steps such as evaporation and magnetron sputtering coating, a diffusion channel of heavy rare earth elements is established, which solves the problem of coercive force of neodymium iron boron magnets at high temperatures, and achieves higher magnetic properties and better Effective utilization of heavy rare earth elements.

CN119446764APending Publication Date: 2025-02-14NINGBO MAGNETIC NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411662134.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The coercive force of existing neodymium iron boron magnets decreases at high temperatures, resulting in an increase in the risk of demagnetization, and the intensive use of heavy rare earth elements is difficult to effectively improve the performance of magnets.

Method used

Using composite diffusion technology, through steps such as evaporation treatment and magnetron sputtering coating, a diffusion channel of heavy rare earth elements is established to achieve efficient diffusion between grain boundaries and improve the coercive force of the magnet.

Benefits of technology

It significantly improves the coercive force of neodymium iron boron magnets at high temperatures, reduces the risk of demagnetization, and improves the utilization rate of heavy rare earth elements, achieving higher magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005143693160000121
    Figure BDA0005143693160000121
Patent Text Reader

Abstract

The invention discloses a method for preparing a neodymium iron boron permanent magnet through composite diffusion, and relates to the technical field of rare earth permanent magnet material processing. The method comprises the following steps: step 1, weighing a main alloy material and an auxiliary alloy material; secondly, the main alloy material is smelted and cast into a throwing piece through a piece casting furnace, and then the throwing piece is subjected to annealing treatment. According to the invention, through a composite grain boundary diffusion technology, evaporation treatment is firstly carried out to obtain an intermediate-state magnet, so that the demagnetization exchange coupling effect between adjacent main phase grains is enhanced, and a channel beneficial to subsequent diffusion of heavy rare earth elements is also formed; and then complete diffusion between grain boundaries is achieved, the maximum diffusion depth is achieved, and the best diffusion effect is achieved through subsequent aging treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth permanent magnet material processing, and particularly relates to a method for preparing NdFeB permanent magnets by composite diffusion. Background Art

[0002] Neodymium iron boron (NdFeB) is the most powerful rare earth permanent magnet material currently. It has a high magnetic energy product (8MGOe-64MGOe), good coercivity (Hcj) and high temperature resistance. Products are widely used in electric vehicles, wind power generation, variable frequency air conditioners, nuclear magnetic resonance, optical disk drives, instruments and meters, mineral processing, toys and other fields.

[0003] In recent years, the rapid development of industries such as electric vehicles and wind power generation has led to an increasing demand for NdFeB magnets that can be used at high temperatures. However, the coercivity of NdFeB magnets decreases with increasing temperature, and the reduction in coercivity at high temperatures increases the risk of magnet demagnetization. In order to improve the high-temperature coercivity of NdFeB magnets, it is generally achieved by partially replacing the light rare earth element Nd with heavy rare earth elements Dy or Tb. Due to the scarcity of heavy rare earth resources and cost considerations, the intensive utilization of heavy rare earths is a problem that needs to be solved at present.

[0004] At present, grain boundary diffusion of heavy rare earths has been widely studied as a method for intensive utilization of heavy rare earths. Through the grain boundary diffusion process, heavy rare earths can be concentrated near the grain boundaries of sintered NdFeB. The amount of heavy rare earths used is small, but the coercivity can be significantly improved while avoiding a significant reduction in remanence. Therefore, compared with the traditional method of adding heavy rare earth elements during smelting, the grain boundary diffusion method is more conducive to obtaining sintered NdFeB magnets with high comprehensive performance.

[0005] After years of development, grain boundary diffusion has developed various processes such as sputtering, evaporation, coating, and electrodeposition. Diffusion sources include heavy rare earth elements and alloys, hydrides, fluorides, oxides, etc. In these processes, except for the evaporation process, the heavy rare earth or its compounds are concentrated on the surface of the product. During the diffusion process, the heavy rare earth will inevitably quickly enter the main phase of the surface area, which will eventually reduce the remanence of the magnet and cause serious waste of heavy rare earth. However, since evaporation does not concentrate heavy rare earth or its compounds on the surface of the product, but supplies dysprosium vapor to the magnet at a uniform speed during the diffusion process, the heavy rare earth will quickly penetrate into the interior of the magnet through the grain boundaries, thereby achieving a better diffusion depth and diffusion effect than other diffusion processes. However, due to the high sensitivity of the evaporation process to the furnace temperature and vacuum degree, the control is difficult, resulting in poor consistency in product weight gain, and it is easy to cause sticking. In addition, the evaporation process has low production efficiency and can only do dysprosium evaporation. Therefore, only a very small number of manufacturers are currently using evaporation technology for batch production.

[0006] Based on this, a method for preparing NdFeB permanent magnets by composite diffusion is proposed, which can improve the diffusion efficiency and utilization rate of heavy rare earth elements and optimize the diffusion effect of heavy rare earth elements. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing NdFeB permanent magnets by composite diffusion, so as to solve the problems raised in the above background technology.

[0008] In order to solve the above technical problems, the present invention is achieved through the following technical solutions:

[0009] The present invention is a method for preparing a NdFeB permanent magnet by composite diffusion, comprising the following steps:

[0010] Step 1: Weigh the main alloy material and the secondary alloy material;

[0011] Step 2: The main alloy material is melted and cast into a slab in a slab casting furnace, and then the slab is annealed, and then the slab is subjected to hydrogen crushing and air flow grinding to prepare a main alloy powder with an average particle size of 2-5 microns, and X90 / X10 is less than 5;

[0012] Step 3: The secondary alloy material is melted in a sheet casting furnace, refined for 3-10 minutes, and cast into 0.1-0.5 mm sheets. The sheets are hydrogen crushed and jet milled to prepare secondary alloy powder with an average particle size of 1-2 microns;

[0013] Step 4: Take 90% of the main alloy powder and 10% of the secondary alloy powder, mix and stir them under the protection of high-purity nitrogen with a content of more than 99.99%, and the stirring time is 4-8 hours;

[0014] Step 5: Isostatic Pressing: The blank wrapped in plastic film and vacuum-sealed is placed in an isostatic press. Under an oil pressure of 150-300 MPa, the density of the blank is increased to 4.4-4.8 g / cm3;

[0015] Step 6: Sintering and tempering.

[0016] Furthermore, the main alloy material in step 1 includes the following raw materials:

[0017] Neodymium, praseodymium, boron, copper, cobalt, gallium, zirconium, iron;

[0018] Secondary alloy materials include the following raw materials:

[0019] Cerium, dysprosium, iron, aluminum.

[0020] Furthermore, the mass percentage of each raw material in the main alloy material is as follows:

[0021] Neodymium praseodymium 28.11wt%, boron 1.00wt%, copper 0.22wt%, cobalt 0.22wt%, gallium 0.11wt%, zirconium 0.11wt%, iron 70.15wt%;

[0022] The mass percentages of the raw materials in the secondary alloy material are as follows:

[0023] Cerium 60wt%, dysprosium 2wt%, iron 37wt%, aluminum 1wt%.

[0024] Furthermore, the annealing treatment in step 2 is performed at a temperature of 900° C. and for a period of 5 hours.

[0025] Furthermore, the sintering and tempering in step six includes the following steps:

[0026] Under nitrogen protection, the vacuum bag and film are peeled off, a graphite box is placed, and the furnace is quickly put into use. After the vacuum is evacuated to below 5.0*10-1Pa, the temperature is raised. When the temperature reaches 800-900℃, the temperature is kept for 4 hours to reduce the vacuum degree to below 10-1Pa. The temperature is then raised to 1075℃ for sintering for 4 hours. After the sintering is completed, argon is filled and cooled to below 100℃. The temperature is raised to 890℃ and kept for 2 hours for primary tempering. After the holding is completed, argon is filled and cooled to below 80℃. The temperature is raised to 500℃ in a vacuum state and kept for 4 hours for secondary tempering. After the holding is completed, argon is filled and cooled to below 60℃ for removal from the furnace.

[0027] Furthermore, the method further comprises step seven: evaporation treatment:

[0028] The sintered NdFeB magnet prepared in the previous step is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and then cleaned with alcohol; then the products are arranged from bottom to top in the molybdenum box in the manner of molybdenum mesh + dysprosium plate + molybdenum mesh + product + molybdenum mesh + dysprosium plate + molybdenum mesh + product + ... + product + molybdenum mesh + dysprosium plate + molybdenum mesh, and put into a vacuum diffusion furnace. After evacuating to below 0.001Pa, the temperature is raised to 820 degrees and kept warm for 10 hours; after the insulation is completed, argon is filled and cooled to below 100 degrees, and then evacuated to below 0.001Pa and then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, argon is filled and cooled to room temperature to obtain an intermediate magnet.

[0029] Furthermore, the method further comprises step eight: magnetron sputtering coating:

[0030] The intermediate state magnet is taken out and its surface is treated with a flat-top laser beam that does not damage the performance of the matrix to remove surface oxides, nitrides, carbides and other high-melting point compounds that hinder grain boundary diffusion; then the magnet is coated with dysprosium by magnetron sputtering to increase the weight of the magnet by 0.15% dysprosium on each oriented surface and 0.3% dysprosium in total.

[0031] Furthermore, it also includes step nine: grain boundary diffusion:

[0032] The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

[0033] Furthermore, it also includes step seven of magnetron sputtering coating and step eight of grain boundary diffusion;

[0034] The step seven magnetron sputtering coating comprises the following steps:

[0035] The sintered NdFeB magnet prepared in the previous step is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and then cleaned with alcohol. Then, the magnet is plated with dysprosium by magnetron sputtering, so that each side of the magnet orientation surface increases 0.25% dysprosium and the total weight of the magnet increases 0.5% dysprosium.

[0036] The step eight grain boundary diffusion comprises the following steps:

[0037] The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

[0038] The present invention has the following beneficial effects:

[0039] The present invention uses composite grain boundary diffusion technology, firstly performs evaporation treatment to obtain an intermediate state magnet, which not only enhances the demagnetization exchange coupling effect between adjacent main phase grains, but also forms a channel that is conducive to the subsequent diffusion of heavy rare earth elements; the subsequent grain boundary diffusion, thanks to the establishment of the diffusion channel in the previous step, can quickly enter the interior of the magnet through the grain boundary channel even if a large amount of heavy rare earth or alloy compounds are accumulated on the surface, and will not enter the interior of the main phase at the surface of the magnet, achieving complete inter-grain boundary diffusion, achieving the maximum diffusion depth, and achieving the best diffusion effect through subsequent aging treatment. Moreover, this composite diffusion scheme, even if terbium elements and alloy compounds are used for diffusion, can also achieve the same diffusion depth and diffusion effect as evaporation diffusion, thereby greatly improving the coercive force of the magnet. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] Embodiment 1:

[0042] A method for preparing a NdFeB permanent magnet by composite diffusion, comprising the following steps:

[0043] Step 1: First, weigh the main alloy material and the secondary alloy material according to the raw material ratio. The main alloy material specifically includes the following raw materials in mass percentage: 28.11wt% of praseodymium and neodymium, 1.00wt% of boron, 0.22wt% of copper, 0.22wt% of cobalt, 0.11wt% of gallium, 0.11wt% of zirconium, and 70.15wt% of iron; the secondary alloy material specifically includes the following raw materials in mass percentage: 60wt% of cerium, 2wt% of dysprosium, 37wt% of iron, and 1wt% of aluminum;

[0044] Step 2: The main alloy material is melted and cast into a slab in a slab casting furnace, and then the slab is annealed at a temperature of 900°C for 5 hours; then the slab is hydrogen crushed and jet milled to prepare a main alloy powder with an average particle size (SMD) of 2-5 microns, and X90 / X10 is less than 5;

[0045] Step 3: The secondary alloy material is melted in a sheet casting furnace for 3-10 minutes, and then cast into a sheet of 0.1-0.5 mm. Since the alloy has a strong amorphous forming ability, it is very easy to form an amorphous structure and a nanocrystalline structure at a cooling rate of nearly 1000°C / S in a conventional sheet casting furnace; then the sheet is hydrogen crushed and jet milled to prepare a secondary alloy powder with an average particle size of 1-2 microns;

[0046] Step 4: Take 90% of the main alloy powder and 10% of the secondary alloy powder, mix and stir them under the protection of high-purity nitrogen with a content of more than 99.99%, and the stirring time is 4-8 hours;

[0047] Step 5: Isostatic Pressing: The blank wrapped in plastic film and vacuum-sealed is placed in an isostatic press. Under an oil pressure of 150-300 MPa, the density of the blank is increased to 4.4-4.8 g / cm3;

[0048] Step 6: Sintering and tempering:

[0049] Under nitrogen protection, the vacuum bag and film are peeled off, a graphite box is placed, and the furnace is quickly put into use. After the vacuum is evacuated to below 5.0*10-1Pa, the temperature is raised. When the temperature reaches 800-900℃, the temperature is kept for 4 hours to reduce the vacuum degree to below 10-1Pa. The temperature is then raised to 1075℃ for sintering for 4 hours. After the sintering is completed, argon is filled and cooled to below 100℃. The temperature is raised to 890℃ and kept for 2 hours for primary tempering. After the holding is completed, argon is filled and cooled to below 80℃. The temperature is raised to 500℃ in a vacuum state and kept for 4 hours for secondary tempering. After the holding is completed, argon is filled and cooled to below 60℃ for removal from the furnace.

[0050] Step 7: Evaporation treatment

[0051] The sintered NdFeB magnet prepared by the above process is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and cleaned with alcohol. Then the products are arranged from bottom to top in the molybdenum box in the form of molybdenum mesh + dysprosium plate + molybdenum mesh + product + molybdenum mesh + dysprosium plate + molybdenum mesh + product + ... + product + molybdenum mesh + dysprosium plate + molybdenum mesh, and placed in a vacuum diffusion furnace. After evacuating to below 0.001Pa, the temperature is raised to 820 degrees and kept warm for 10 hours. During this process, dysprosium evaporates to the surface of the product and diffuses into the interior of the product to form a channel that is conducive to subsequent diffusion. However, due to the low temperature, the proportion of dysprosium entering the product is not large, accounting for about 0.05-0.2% of the weight of the magnet. After the insulation is completed, argon is filled and air-cooled to below 100 degrees, and then evacuated to below 0.001Pa and heated to 500 degrees for 5 hours for aging treatment. After the insulation is completed, argon is filled and air-cooled to room temperature to obtain an intermediate magnet.

[0052] Step 8: Magnetron sputtering coating

[0053] The intermediate magnet is taken out and its surface is treated with a flat-top laser beam that does not damage the performance of the matrix to remove high-melting-point compounds such as surface oxides, nitrides, and carbides that hinder grain boundary diffusion. Then the magnet is plated with a dysprosium film by magnetron sputtering, so that each side of the magnet orientation surface increases by 0.15% dysprosium and the total weight of the magnet increases by 0.3%.

[0054] Step 9: Grain Boundary Diffusion

[0055] The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

[0056] The intermediate state magnet is obtained by subjecting the product to a vapor deposition treatment similar to vapor deposition grain boundary diffusion and an aging treatment, and utilizing vapor deposition diffusion to introduce a small amount of heavy rare earth dysprosium or dysprosium alloy into the grain boundaries of the matrix without entering the interior of the main phase to affect the remanence, thereby promoting uniform distribution of the grain boundary phase and providing a favorable diffusion channel for subsequent heavy rare earth or alloy diffusion; and by subjecting the surface of the intermediate state magnet to a surface treatment using a flat-top laser beam that does not damage the performance of the matrix to remove high-melting-point compounds such as surface oxides, nitrides, and carbides that hinder grain boundary diffusion; and finally, subjecting the surface-treated magnet to any form of grain boundary diffusion and an aging treatment to obtain a final magnet.

[0057] Embodiment 2:

[0058] A method for preparing a NdFeB permanent magnet by composite diffusion, comprising the following steps:

[0059] Step 1: First, weigh the main alloy material and the secondary alloy material according to the raw material ratio. The main alloy material specifically includes the following raw materials in mass percentage: 28.11wt% of praseodymium and neodymium, 1.00wt% of boron, 0.22wt% of copper, 0.22wt% of cobalt, 0.11wt% of gallium, 0.11wt% of zirconium, and 70.15wt% of iron; the secondary alloy material specifically includes the following raw materials in mass percentage: 60wt% of cerium, 2wt% of dysprosium, 37wt% of iron, and 1wt% of aluminum;

[0060] Step 2: The main alloy material is melted and cast into a slab in a slab casting furnace, and then the slab is annealed at a temperature of 900°C for 5 hours; then the slab is hydrogen crushed and jet milled to prepare a main alloy powder with an average particle size (SMD) of 2-5 microns, and X90 / X10 is less than 5;

[0061] Step 3: The secondary alloy material is melted in a sheet casting furnace for 3-10 minutes, and then cast into a sheet of 0.1-0.5 mm. Since the alloy has a strong amorphous forming ability, it is very easy to form an amorphous structure and a nanocrystalline structure at a cooling rate of nearly 1000°C / S in a conventional sheet casting furnace; then the sheet is hydrogen crushed and jet milled to prepare a secondary alloy powder with an average particle size of 1-2 microns;

[0062] Step 4: Take 90% of the main alloy powder and 10% of the secondary alloy powder, mix and stir them under the protection of high-purity nitrogen with a content of more than 99.99%, and the stirring time is 4-8 hours;

[0063] Step 5: Isostatic Pressing: The blank wrapped in plastic film and vacuum-sealed is placed in an isostatic press. Under an oil pressure of 150-300 MPa, the density of the blank is increased to 4.4-4.8 g / cm3;

[0064] Step 6: Sintering and tempering:

[0065] Under nitrogen protection, the vacuum bag and film are peeled off, a graphite box is placed, and the furnace is quickly put into use. After the vacuum is evacuated to below 5.0*10-1Pa, the temperature is raised. When the temperature reaches 800-900℃, the temperature is kept for 4 hours to reduce the vacuum degree to below 10-1Pa. The temperature is then raised to 1075℃ for sintering for 4 hours. After the sintering is completed, argon is filled and cooled to below 100℃. The temperature is raised to 890℃ and kept for 2 hours for primary tempering. After the holding is completed, argon is filled and cooled to below 80℃. The temperature is raised to 500℃ in a vacuum state and kept for 4 hours for secondary tempering. After the holding is completed, argon is filled and cooled to below 60℃ for removal from the furnace.

[0066] Step 7: Magnetron sputtering coating

[0067] The sintered NdFeB magnet prepared by the above process is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and then cleaned with alcohol. The magnet is then plated with dysprosium by magnetron sputtering, so that the dysprosium weight of each oriented surface of the magnet increases by 0.25% and the total weight of the magnet increases by 0.5%.

[0068] Step 8: Grain Boundary Diffusion

[0069] The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

[0070] Comparative Example:

[0071] Step 1: Ingredients: weigh the raw materials according to the specified proportion, formula: PrNd: 25.3wt%, Ce: 6wt%, Dy: 0.2wt%, B: 0.9wt%, Cu: 0.2wt%, Co: 0.2wt%, Ga: 0.1wt%, Zr: 0.1wt%, Fe balance.

[0072] Step 2: Melting and casting into slabs in a slab casting furnace, and then preparing the slabs into alloy powders with an average particle size (SMD) of 2 to 5 microns and X90 / X10 less than 5 through hydrogen crushing and air flow grinding, and adding agents and stirring;

[0073] Step 3: Place the stirred powder into a molding press mold under nitrogen protection, and add a magnetic field for orientation molding to obtain a green body with a molding density of 3.6 to 4.2 g / cm3;

[0074] Step 4: Isostatic Pressing: The blank wrapped in plastic film and vacuum-sealed is placed in an isostatic press. Under an oil pressure of 150-300 MPa, the density of the blank is further increased to 4.4-4.8 g / cm3;

[0075] Step 5: Sintering and tempering: Under nitrogen protection, peel off the vacuum bag and film, put in the graphite box, quickly enter the furnace, evacuate to below 5.0*10-1Pa and then start heating. When the temperature reaches 800-900℃, keep it for 4 hours to reduce the vacuum degree to below 10-1Pa, continue to heat it to 1075℃ and sinter for 4 hours; after sintering, fill with argon and cool to below 100℃, heat it to 890℃ and keep it for 2 hours for primary tempering, after keeping it for argon, cool it to below 80℃, heat it to 500℃ in vacuum state and keep it for 4 hours for secondary tempering, after keeping it for argon, cool it to below 60℃ and take it out of the furnace.

[0076] Step 6: Evaporation treatment

[0077] The sintered NdFeB magnet prepared by the above process is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and cleaned with alcohol. Then the products are arranged from bottom to top in the molybdenum box in the form of molybdenum mesh + dysprosium plate + molybdenum mesh + product + molybdenum mesh + dysprosium plate + molybdenum mesh + product + ... + product + molybdenum mesh + dysprosium plate + molybdenum mesh, and placed in a vacuum diffusion furnace. After evacuating to below 0.001Pa, the temperature is raised to 820 degrees and kept warm for 10 hours. During this process, dysprosium evaporates to the surface of the product and diffuses into the interior of the product to form a channel that is conducive to subsequent diffusion. However, due to the low temperature, the proportion of dysprosium entering the product is not large, accounting for about 0.05-0.2% of the weight of the magnet. After the insulation is completed, argon is filled and air-cooled to below 100 degrees, and then evacuated to below 0.001Pa and heated to 500 degrees for 5 hours for aging treatment. After the insulation is completed, argon is filled and air-cooled to room temperature to obtain an intermediate magnet.

[0078] Step 7: Magnetron sputtering coating

[0079] The intermediate magnet is taken out and its surface is treated with a flat-top laser beam that does not damage the performance of the matrix to remove high-melting-point compounds such as surface oxides, nitrides, and carbides that hinder grain boundary diffusion. Then the magnet is plated with a dysprosium film by magnetron sputtering, so that each side of the magnet orientation surface increases by 0.15% dysprosium and the total weight of the magnet increases by 0.3%.

[0080] Step 8: Grain Boundary Diffusion

[0081] The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

[0082] The intermediate state magnet is obtained by subjecting the product to a vapor deposition treatment similar to vapor deposition grain boundary diffusion and an aging treatment, and utilizing vapor deposition diffusion to introduce a small amount of heavy rare earth dysprosium or dysprosium alloy into the grain boundaries of the matrix without entering the interior of the main phase to affect the remanence, thereby promoting uniform distribution of the grain boundary phase and providing a favorable diffusion channel for subsequent heavy rare earth or alloy diffusion; and by subjecting the surface of the intermediate state magnet to a surface treatment using a flat-top laser beam that does not damage the performance of the matrix to remove high-melting-point compounds such as surface oxides, nitrides, and carbides that hinder grain boundary diffusion; and finally, subjecting the surface-treated magnet to any form of grain boundary diffusion and an aging treatment to obtain a final magnet.

[0083] The sintered NdFeB initial magnets and diffused magnets prepared by the methods described in Example 1 and Example 2 and the comparative example were measured using a permanent magnet property measuring instrument, and their performance is as follows:

[0084] Table 1

[0085]

[0086] It can be seen from Table 1 that the permanent magnet prepared by the method described in Example 1 has higher magnetic properties than the permanent magnet prepared in the comparative example in terms of remanence, coercive force and magnetic energy product, and higher Hk / Hcj, indicating that the magnet prepared by the method of Example 1 has better consistency.

[0087] Furthermore, a grain boundary diffusion method is provided for improving the diffusion efficiency of heavy rare earth elements, optimizing the diffusion effect of heavy rare earth elements, and improving the utilization rate of heavy rare earth elements, thereby effectively improving the coercive force of magnets.

[0088] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0089] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing NdFeB permanent magnets by composite diffusion, characterized in that: The following steps are involved: Step 1: Weigh the main alloy material and the secondary alloy material; Step 2: The main alloy material is melt-refined and then spun to obtain spun flakes, and the spun flakes are then subjected to hydrogen crushing and jet milling to prepare the main alloy powder with an average particle size of 2-5 microns and X90 / X10 less than 5; Step 3: melt-refining the secondary alloy material and spinning it to obtain spinning flakes, and then subjecting the flakes to hydrogen crushing and jet milling to prepare secondary alloy powder with an average particle size of 1-2 microns; Step 4: Take 90% of the main alloy powder and 10% of the secondary alloy powder, mix and stir them under the protection of high-purity nitrogen with a content of more than 99.99%, and the stirring time is 4-8 hours; Step 5: Isostatic Pressing: The blank wrapped in plastic film and vacuum-sealed is placed in an isostatic press. Under an oil pressure of 150-300 MPa, the density of the blank is increased to 4.4-4.8 g / cm3; Step 6: Sintering and tempering.

2. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 1, characterized in that: The main alloy material in step 1 includes the following components: Neodymium, praseodymium, boron, copper, cobalt, gallium, zirconium, iron; The secondary alloy materials include the following components: Cerium, dysprosium, iron, aluminum.

3. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 2, characterized in that: The mass percentages of the components in the main alloy material are as follows: Neodymium praseodymium 28.11wt%, boron 1.00wt%, copper 0.22wt%, cobalt 0.22wt%, gallium 0.11wt%, zirconium 0.11wt%, iron 70.15wt%; The mass percentages of the components in the secondary alloy material are as follows: Cerium 60wt%, dysprosium 2wt%, iron 37wt%, aluminum 1wt%.

4. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 1, characterized in that: The sintering and tempering in step 6 includes the following steps: Under nitrogen protection, the vacuum bag and film are peeled off, a graphite box is placed, and the furnace is quickly put into use. After the vacuum is evacuated to below 5.0*10-1Pa, the temperature is raised. When the temperature reaches 800-900℃, the temperature is kept for 4 hours to reduce the vacuum degree to below 10-1Pa. The temperature is then raised to 1075℃ for sintering for 4 hours. After the sintering is completed, argon is filled and cooled to below 100℃. The temperature is raised to 890℃ and kept for 2 hours for primary tempering. After the holding is completed, argon is filled and cooled to below 80℃. The temperature is raised to 500℃ in a vacuum state and kept for 4 hours for secondary tempering. After the holding is completed, argon is filled and cooled to below 60℃ for removal from the furnace.

5. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 4, characterized in that: Also includes step seven: evaporation treatment: The sintered NdFeB magnet prepared in the previous step is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and then cleaned with alcohol; then the products are arranged from bottom to top in the molybdenum box in the manner of molybdenum mesh + dysprosium plate + molybdenum mesh + product + molybdenum mesh + dysprosium plate + molybdenum mesh + product + ... + product + molybdenum mesh + dysprosium plate + molybdenum mesh, and put into a vacuum diffusion furnace. After evacuating to below 0.001Pa, the temperature is raised to 820 degrees and kept warm for 10 hours; after the insulation is completed, argon is filled and cooled to below 100 degrees, and then evacuated to below 0.001Pa and then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, argon is filled and cooled to room temperature to obtain an intermediate magnet.

6. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 5, characterized in that: Also includes step eight: magnetron sputtering coating: The intermediate state magnet is taken out and its surface is treated with a flat-top laser beam that does not damage the performance of the matrix to remove surface oxides, nitrides, carbides and other high-melting point compounds that hinder grain boundary diffusion; then the magnet is coated with dysprosium by magnetron sputtering to increase the weight of the magnet by 0.15% dysprosium on each oriented surface and 0.3% dysprosium in total.

7. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 6, characterized in that: Also includes step nine: grain boundary diffusion: The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

8. The method for preparing NdFeB permanent magnets by composite diffusion according to claim 4, characterized in that: It also includes step seven of magnetron sputtering coating and step eight of grain boundary diffusion; The step seven magnetron sputtering coating comprises the following steps: The sintered NdFeB magnet prepared in the previous step is used as the initial magnet. After being processed into 10*10*8mm, the surface of the magnet is pickled and then cleaned with alcohol. Then, the magnet is plated with dysprosium by magnetron sputtering, so that each side of the magnet orientation surface increases 0.25% dysprosium and the total weight of the magnet increases 0.5% dysprosium. The step eight grain boundary diffusion comprises the following steps: The diffused magnet is placed in a vacuum diffusion furnace, evacuated to below 0.001Pa, then heated to 900 degrees and kept warm for 20 hours. After the insulation is completed, it is cooled to below 100 degrees with argon air. Then, it is evacuated to below 0.001Pa, then heated to 500 degrees and kept warm for 5 hours for aging treatment. After the insulation is completed, it is cooled to room temperature with argon air to obtain the final magnet.

Citation Information

Cited By

  • Neodymium-iron-boron magnet and preparation method thereof

    CN121171773A